2013
DOI: 10.2215/cjn.01420213
|View full text |Cite
|
Sign up to set email alerts
|

Medication Reconciliation and Therapy Management in Dialysis-Dependent Patients

Abstract: SummaryPatients with ESRD undergoing dialysis have highly complex medication regimens and disproportionately higher total cost of care compared with the general Medicare population. As shown by several studies, dialysis-dependent patients are at especially high risk for medication-related problems. Providing medication reconciliation and therapy management services is critically important to avoid costs associated with medication-related problems, such as adverse drug events and hospitalizations in the ESRD po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 32 publications
(35 reference statements)
1
71
1
9
Order By: Relevance
“…Unlike other mobile applications, we believe that this is the only mobile application for outpatient use that supports patient-driven medication reconciliation with a feedback loop to correct errors (10,21,22). Communication of medication-related information is particularly crucial for this patient population, because patients frequently experience medication errors as a result of fragmented communication between multiple prescribers (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other mobile applications, we believe that this is the only mobile application for outpatient use that supports patient-driven medication reconciliation with a feedback loop to correct errors (10,21,22). Communication of medication-related information is particularly crucial for this patient population, because patients frequently experience medication errors as a result of fragmented communication between multiple prescribers (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that dialysis-dependent patients are at an especially elevated risk of medication-related problems, medication discrepancies, and drug-record discrepancies. 3,4,6,7,15,16,[20][21][22][23] In the current 2-year study, the mean number of medication discrepancies identified through ambulatory medication reconciliation was 1.31 per hemodialysis patient and 0.65 per reconciliation process. A previous study reported drug record discrepancies of 1.7 (SD 1.3) per patient when information gathered from the patient was compared with information in an electronic medical record.…”
Section: Discussionmentioning
confidence: 99%
“…17 Providing ambulatory medication reconciliation is critically important to reducing the risk of harm associated with medication discrepancies, such as adverse drug events and admission to hospital. 3 The majority of survey respondents reported that ambulatory medication reconciliation improved the quality of care that practitioners provided to their dialysis patients. As part of our process, a copy of each patient's reconciliation form is sent to the patient and to the relevant community pharmacy and family physician.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of pharmacists has been shown to not only identify actual and potential MRPs, but to reduce rehospitalizations and lengths of stay of dialysis patients. 7,8 In another common scenario, the ESRD patient is admitted for an infectious cause or sepsis, receives appropriate intravenous antibiotics after positive wound or blood cultures, and is discharged as soon as clinical symptoms improve, with the presumption that the same antibiotic regimen can be continued in the dialysis unit. Unfortunately, in many cases, the information about the specific intravenous antibiotic is not transmitted to the dialysis facility in time for the facility to order the antibiotics.…”
mentioning
confidence: 99%